2019
DOI: 10.1142/s1793524519500785
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic profile of a mutualistic model on a periodically evolving domain

Abstract: In order to investigate the impact of periodically evolving domain on the mutualism interaction of two species, we study a mutualistic model on a periodically evolving domain. To overcome the difficulty caused by the advection and dilution terms, we transform the model to a reaction–diffusion problem in a fixed domain. By means of eigenvalue problems, the threshold parameters are introduced. The asymptotic profiles of the solutions on an evolving domain are studied by using the threshold parameters and the upp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In [31], Jiang and Wang studied the impact of periodic evolution on the singlespecies diffusion logistic model. Asymptotic profile of a mutualistic model on a periodically evolving domain has been investigated by Adam et al in [33]. e diffusive model for Aedes aegypti mosquito on a periodically evolving domain has been considered by Zhang and Lin in [32].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In [31], Jiang and Wang studied the impact of periodic evolution on the singlespecies diffusion logistic model. Asymptotic profile of a mutualistic model on a periodically evolving domain has been investigated by Adam et al in [33]. e diffusive model for Aedes aegypti mosquito on a periodically evolving domain has been considered by Zhang and Lin in [32].…”
Section: Discussionmentioning
confidence: 99%
“…eir results indicated that the asymptotic spreading speed of the WNv model with free boundary is strictly less than that of the corresponding model in Lewis et al [4]. For the domain changing with known boundary, there are also some papers, for instance, [27][28][29][30] for a growing domain and [31][32][33][34] for a periodically evolving domain. In [31], the authors introduced the periodically evolving domain into a single-species diffusion logistic model and studied the influence of periodic evolution on the survival and extinction of species.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Owing to the turnover of the four seasons, the evolving of domain is usually periodic. In recent years, some scholars have studied mathematical models on a periodically evolving domain, for example, an SIS epidemic model [28], a mutualistic model [1], an Aedes aegypti mosquito model [40], a dengue fever model [41], and so on. In this paper, we consider the following problem        S t − d S ∆S = a(x)S − b(x)S 2 − β(x)f (S, I)I + γ(x)I, x ∈ Ω, t > 0, I t − d I ∆I = β(x)f (S, I)I − γ(x)I, x ∈ Ω, t > 0, ∂S ∂ν = ∂I ∂ν = 0, x ∈ ∂Ω, t > 0, S(x, 0) = S 0 (x), I(x, 0) = I 0 (x),…”
Section: Introductionmentioning
confidence: 99%